The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1111/j.1939-0025.1985.tb02701.x
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about the threat of nuclear war: Relevance to mental health.

Abstract: Ontario students in grades 7–13 responded to open‐ended and multiple‐choice questions about future concerns, particularly unemployment, job/career plans, and the nuclear threat. Although worries about nuclear war were more frequent than those in other areas, their expression was associated with a sense of social efficacy rather than with feelings of helplessness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 9 publications
6
20
0
Order By: Relevance
“…Canadian researchers documented similar findings in two studies carried out with over 1,000 Canadian children in grades 7 to 13 (5). They found that 64 percent of grade 7 students reported worrying about nuclear war while only 36 percent of grade 13 students reported such worries.…”
supporting
confidence: 61%
“…Canadian researchers documented similar findings in two studies carried out with over 1,000 Canadian children in grades 7 to 13 (5). They found that 64 percent of grade 7 students reported worrying about nuclear war while only 36 percent of grade 13 students reported such worries.…”
supporting
confidence: 61%
“…This finding emerged in many countries, including the United States, the Soviet Union, Canada, England, Hungary, Ireland, Italy, and Norway (Chivian, 1985;Christie & Murphy, 1990;Goldberg et al, 1985;Goldenring & Doctor, 1985;Goldenring et al, 1989;Hamilton, van Mouwerick, Beauvais, & Keilin, 1988;Raundalen & Finney, 1986;Tudge & Chivian, 1989;cf. This finding emerged in many countries, including the United States, the Soviet Union, Canada, England, Hungary, Ireland, Italy, and Norway (Chivian, 1985;Christie & Murphy, 1990;Goldberg et al, 1985;Goldenring & Doctor, 1985;Goldenring et al, 1989;Hamilton, van Mouwerick, Beauvais, & Keilin, 1988;Raundalen & Finney, 1986;Tudge & Chivian, 1989;cf.…”
Section: Feelingsmentioning
confidence: 99%
“…That children and younger adolescents reported more worry than older adolescents and young adults may be partially explained by the finding that the latter group is more inclined not to report worrying about anything (Tudge & Chivian, 1989). As adolescents prepare for adulthood, a whole range of new issues must be considered (finding a career, getting married and raising a family), and consequently other "real life" issues such as inflation or unemployment are of primary importance for the first time (Christie & Murphy, 1990;Goldberg et al, 1985;Van Hoorn et al, 1989). In addition, the rise in concern about nuclear war over time was not simply a result of greater concern about the future in general (Diamond & Bachman, 1986).…”
Section: Feelingsmentioning
confidence: 99%
“…However, other investigators have either found the frequency of worry about nuclear war to be unrelated to measures of adjustment (Wrightsman, 1970), or that adolescents who are most worried actually appear to be more mature, perform better in school, and report higher self-esteem (see Goldenring & Doctor, 1986). Moreover, in a recent study involving 2,000 Canadian students, researchers found that those who worried most about nuclear war were also those who were most concerned with unemployment and future jobkareer plans (Goldberg et al, 1985). The authors concluded that "thoughts about nuclear war have not led these students to 'foreclose' their own futures" and "it is inappropriate to assume that existence of fear or worry is necessarily a negative response or that it is damaging to mental health" (pp.…”
mentioning
confidence: 99%
“…For example, Goldenring and Doctor (1986) asked subjects to list their three greatest worries, while Mayton (1986) defined "spontaneous concern" as mentioning nuclear war within five presentations of two incomplete sentences. Alternatively, Wrightsman (1970) asked subjects to report their frequency of worry about war on a single 5-point scale, and Goldberg et al (1985) had subjects indicate on a 4-point scale how often they felt fearful and anxious about nuclear war. Although these methods provide important information regarding the salience of the nuclear issue and the frequency of nuclear-related worry, the reliability of such measurement strategies remains undocumented and data regarding the intensity of immediate affective reactions are not currently available in the literature.…”
mentioning
confidence: 99%